Numerical Solution of High Order Bernoulli Boundary Value Problems - F. Costabile; A. Napoli (Journal of Applied Mathematics)
For the numerical solution of high order boundary value problems with special boundary conditions a general procedure to determine collocation methods is derived and studied. Computation of the integrals which appear in the coefficients is generated by a recurrence formula and no integrals are involved in the calculation. Several numerical examples are presented to demonstrate the practical usefulness of the proposed method.